Karakteristik Sifat Kimia Tanah Lahan Gambut di Perkebunan Kencur Desa Sei Baru Kecamatan Panai Hilir Kabupaten Labuhanbatu - Siregar, Asnan; Walida, Hilwa; Sitanggang, Kamsia Dorliana; Harahap, Fitra Syawal; Triyanto, Yudi (Agrotechnology Research Journal, 2021)
Farmers in Sei Baru village manage marginal peatlands for producing the galangal. So far, testing of soil characteristics has never been carried out. Fertilization and culture practices are just based on knowledge from generation to generation, so it is important to study the characteristics of soil chemical properties of the peatlands that have been used for producing galangal. The research was conducted from December 2020 until February 2021 in a galangal plantation-grown by the community in Sei Baru Village, Panai Hilir District, Labuhanbatu Regency. The method used was a free grid survey method at the semi-detailed survey level. The implementation of soil sampling of 5 sample points with a distance of 100 meters in the field using a random method spread over a predetermined area. The results showed that the peat soil planted with galangal in Sei Baru Village had a pH of around 4.542, C-org was 52.18%, organic matter was 89.972%, N-total was 1.418%, C/N was 36.852, P-Bray was 963.41 ppm, and K-total was 0.14. Overall, the chemical properties of the soil in galangal plantations Sei Baru Village, Panai Hilir District, Labuhanbatu Regency are in good condition.to increase its fertility for galangal cultivation, it can be done by increasing the pH and potassium in the soil so that it will become more favorable for growing galangal and can be used as a recommendation for galangal fertilization.